E-portfolio MSC indicator for a virtual learning environment - Rahim, Mohd Bekri; Ruhizan, M. Y.; Masran, Saiful Hadi; Nur Yunus, Faizal Amin; Abd Baser, Jamil (Universiti Putra Press, 2017)
This study was conducted to identify indicators for the use of e-portfolio for a virtual learning environment in the Malaysian Skills Certification (MSC) system. The approach is through a modified Delphi technique run in three stages. The first stage is analysis of past research material and documents as guidelines in the development of questionnaire items. In the second and third stages, the developed questionnaire is distributed to experts for approval in determining e-portfolio indicators for implementation of the Malaysian Skills Certification system. The sample selected consists of 11 experts in the field of skills certification in Malaysia. Feedback from the experts was analysed using descriptive statistics (mean, median and interquartile range). The findings identify four elements (Assessment, Personal Space, Exhibition and Learning Management) and 32 indicators through a literature review. In conclusion, there are 22 indicators were identified as necessary for the implementation of the use of the e-portfolio in the Malaysian Skills Certification system.